Large scale underground construction risk assessment using decision aids for tunneling (DAT) - Wong, Kenzo Qi Jun (2017)
Being a tiny island, Singapore is facing problems such as lack of spaces and over-population. Like many other countries, Singapore is actively expanding. However, due to scarce land, Singapore cannot expand outwards but underground. With new and advanced technology emerging, Singapore is looking to optimize land space by developing underground projects. Currently, Singapore has managed to kick-start two major underground projects – the Underground Ammunition Facility (completed in 2008) and Jurong Rock Caverns (Officially opened in 2014). A strategic usage of underground spaces can be very effective. However, more often than not, underground development projects usually involve uncertainties and risks. This is especially true for large-scale projects with high complexity and long life span. A local state developer is also aiming to create an underground network of tunnels for transporting goods between industrial centers and a container port. Hence, this project aims to conduct a risk assessment for the large-scale underground project. This report will first study and discuss the tunnel network and the caverns’ excavation sequences. Then it will identify all the geological and construction uncertainties faced in the underground project, follow by cost estimations for all the required construction activities. The ultimate goal of this project is to provide the decision maker with the expected total project cost as well as time duration, by using a stimulation software – Decision Aids for Tunneling (DAT), to generate a time-cost scatter-gram. In addition, this report will also include the results generated by another similar software, @Risk. A comparison will be made between the results from DAT and @Risk, whereby conclusions can be drawn and this will aid the decision maker in a proper risk assessment for the large-scale underground project.